قَوْلُ الصَّحَابِي عِندَ ابنِ رُشد الحَفِيد المَالِكِي (ت595هـ) وأَثَرُهُ فِي اختِيَارَاتِهِ الفِقهِيَّةِ مِنْ خِلاَلِ كِتَابِهِ بِدَايَةِ المجُتَهِدِ ونِهَايَةِ المُقْتَصِد - غرب, حمزة (University of Eloued جامعة الوادي, 2017)
قام هذا البحث بدراسة: قول الصحابي عند ابن رشد الحفيد المالكي )ت595ه( وأثره في اختياراته الفقهية من خلال كتابه بداية المجتهد ونهاية المقتصد. وقد قُسّمت الدراسة إلى مبحثين: المبحث الأول خُصّص للتعريف بابن رشد الحفيد وكتابه بداية المجتهد ونهاية المقتصد، ثم عُرّج على مفهوم قول الصحابي, وبيان مذاهب العلماء وابن رشد الحفيد في حُجّيته، أما المبحث الثاني فقد كان في دراسة أثر قول الصحابي في اختيارات ابن رشد؛حيث ظهر أثره في أربعة مسائل: قضاء رمضان متتابعا، وطلاق السكران، وميراث ولد الملاعنة، والمتاجرة بمال الوديعة. وقد توصلتِ الدراسة إلى جملة من النتائج لعل أهمها كون مذهب الصحابي ليس حجة عند ابن رشد الحفيد، إلا ما كان قرينة على ثبوت سُنّة، ولكن لم تظهر القرينة في كل موضع اعتمد فيه ابن رشد الحفيد على قول الصحابي. This research work deals with the attiude of Ibn Rushd as regard the Sayimg of the Sahabi in ris book "Bidayet El Mudjtahid and Nihayet El Moktasid". The research work is divided ints two sectons and a conclusion. The first section desls with the autobiography of Ibn Rushd and his book "Bidayet El Mudjtahid and Nihayet El Moktasid" this section alsa deals with an argument as regard the Sahabi's saying in the light of Ibn Rushd and other scholars' given evidence. The second section deals with a study concerning the saying of the "Sahabi" in the light of Ibn Rushds doctrine choices and thus appeared in four issues: the making up of Ramadan days consecutely the durorce of the drunb the mhesitance of achild whase mather is accused of adultery and trading with deposted money It the end the final statement or conclusion reached is sammaried in a mumber of results the most important of which refutes the doctrine of the Sahabi' s syimp because it lackas serpport from am esrdent summa.
مذكرة ماستر تخصص اصول فقه
Keywords: - قول الصحابي - ابن رشد الحفيد - بداية المجتهد ونهاية المقتصد; Sayimg of the Sahabi- Ibn Rushd al Hafid- Bidayet El Mudjtahid and Nihayet El Moktasid